Treatment of Neonatal Purulent Meningitis with a Sulphamethoxazole (SMZ)/Trimethoprim (TMP) Combination - Sumarmo Sumarmo; Mugiyo Mugiyo; Priutomo Priutomo; Sofyan Ismael; Muslim A. Nathin (Indonesian Pediatric Society, 1982)
This paper describes our experience in treating neonatal meningitis with an intravenous Sulphametoxazole/Trimethoprim (SMZ-TMP) combination.Fifteen neonates ranging in age from 6 to 36 days were included in this study. Cerebrospiral fluid isolates were as follows:S. havana (3), S. oranienburg (2) and Haemolytic streptococci (1), the remaining 9 cultures were negative. Those bacteria isolated were all sensitive to SMZ/TMP. A solution of SMZ 80 mg/ml and TMP 16 mg/ml in 40% propylene glycol was used with a daily dose of 10 mgfkg B.W. TMP for the first 3 days followed by 6 mg/kg B.W. TMP for 18 days or longer, divided in two dose given intravenously every 12 hours.Thirteen patients recovered, but two died of neurological complications, one with ventriculitis and the other with a subdural empyema.No hematological or cutaneous or gastrointestinal side effects were observed. The liver and renal function tests performed on 5 out of the 15 patients on the first few days of hospitalization and 3 weeks later were all within normal lirnits. The use of parenteral SMZ-TMP in neonatal meningitis showed an encouraging result considering the fact rthat our previous mortality rate was 60%.